x*y=-3 x+y=7

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[TeX]
[pretty]
[text]
x*y = -3
$$x y = -3$$
x + y = 7
$$x + y = 7$$
Быстрый ответ
[TeX]
$$x_{1} = \frac{7}{2} + \frac{\sqrt{61}}{2}$$
=
$$\frac{7}{2} + \frac{\sqrt{61}}{2}$$
=
7.40512483795333

$$y_{1} = - \frac{\sqrt{61}}{2} + \frac{7}{2}$$
=
$$- \frac{\sqrt{61}}{2} + \frac{7}{2}$$
=
-0.405124837953327
$$x_{2} = - \frac{\sqrt{61}}{2} + \frac{7}{2}$$
=
$$- \frac{\sqrt{61}}{2} + \frac{7}{2}$$
=
-0.405124837953327

$$y_{2} = \frac{7}{2} + \frac{\sqrt{61}}{2}$$
=
$$\frac{7}{2} + \frac{\sqrt{61}}{2}$$
=
7.40512483795333
Численный ответ
[pretty]
[text]
x1 = -0.4051248379533272
y1 = 7.405124837953327
x2 = 7.405124837953327
y2 = -0.4051248379533272